The artistry of John: the Fourth Gospel as narrative christology - Stibbe, Mark (1989)
The present work has two aims. The first aim is to introduce the method of narrative criticism to New Testament scholars and we attempt to do this in Part One. Narrative criticism of the Bible has been practised since the early 1980's, but since that time no one has established the nature and the aims of the method. This thesis is the first work to define what a comprehensive narrative-critical approach to the gospels might entail. It is also the first work to include historical concerns in the narrative-critical programme. The examples of narrative criticism we do have in New Testament studies all assume that narrative criticism must be an a-historical method. We point out the fallacy of this view by drawing attention to the recent sociological studies of the narrative form and to the narrative history debate in History Faculties during the 1960's and 1970's. These two movements in scholarship necessitate an historical dimension to narrative criticism if the narrative form is not to be greatly restricted and over-simplified. In Part One we provide an apology for narrative criticism and we show how future Johannine scholars might examine JOHN as narrative Christology (chapter one), narrative performance (chapter two), community narrative (chapter three) and narrative history (chapter four). In Part Two we provide an illustration of the method at work. Taking the Johannine passion narrative as our text (John 18-19), we show how this part of JOHN might be examined as narrative Christology (chapter five), narrative performance (chapter six), community narrative (chapter seven) and narrative history (chapter eight). This thesis is the first to expose these chapters to a thorough and rigorous literary approach. Our analysis reveals that the fourth evangelist has constructed his passion story with great artistry. We draw particular attention to narrative echo-effects, characterization, tragic mood, the reader's response of "home-coming" and time-shapes in John 18-19. These, and many other narrative strategies, contribute towards the classic, disclosing power of JOHN's story of the death of Jesus.